MECHANICAL CHARACTERIZATION OF POLYMERIC FILMS BASED ON COPOLYMERS OF STYRENE AND BUTYL ACRYLATE OBTAINED BY HETEROGENEOUS POLYMERIZATION IN SEMICONTINUOUS - Neira Velázquez, M. Guadalupe (2021)
The aim of this work was to synthesize copolymers of styrene (St) and butyl acrylate (AB) cross-linked with allyl methacrylate by semicontinuous heterogeneous polymerization in order to study the mechanical properties of the polymeric films prepared from the latexes obtained. Copolymer latexes were stable and nanoparticles with spherical morphology were observed by Transmission Electron Microscopy (TEM). The latexes had final conversions between 92,5 and 97,0%, which were determined by the gravimetric method, and a solids content close to 20%. The nanoparticles of latex had an average diameter of 59,1; 55,1 and 49,0 nm for monomer dosing rates of 0,75; 0,45 and 0,15 g/min, respectively. By means of mechanical characterization of the polymeric films and according to the statistical analysis, it was found that when the monomer dosage rate decreased in the synthesis, the mean particle diameter and molecular weight also decreased, and with it a decrease in its Young's Modulus (MPa).